2021
DOI: 10.1371/journal.pone.0253766
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulate matter exposure results in white matter damage and an inflammatory microglial response in an experimental murine model

Abstract: Exposure to ambient air pollution has been associated with white matter damage and neurocognitive decline. However, the mechanisms of this injury are not well understood and remain largely uncharacterized in experimental models. Prior studies have shown that exposure to particulate matter (PM), a sub-fraction of air pollution, results in neuroinflammation, specifically the upregulation of inflammatory microglia. This study examines white matter and axonal injury, and characterizes microglial reactivity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…However, the combined effect of nPM and BCAS induced a greater increase in oligodendrocyte apoptosis than neuronal apoptosis when compared to FA (700% vs. 200% increase). These data confirm and extend prior studies that demonstrated white matter damage secondary to nPM and increased effects of combined nPM + BCAS exposure on corpus callosum white matter injury (Connor et al, 2021; Liu et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the combined effect of nPM and BCAS induced a greater increase in oligodendrocyte apoptosis than neuronal apoptosis when compared to FA (700% vs. 200% increase). These data confirm and extend prior studies that demonstrated white matter damage secondary to nPM and increased effects of combined nPM + BCAS exposure on corpus callosum white matter injury (Connor et al, 2021; Liu et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Activated microglia upregulate iNOS and produce both NO and reactive oxygen species (ROS) (Kawabori & Yenari, 2015). Microglial activation has been previously demonstrated in the setting of nPM, BCAS, and joint nPM + BCAS exposures (Babadjouni et al, 2018; Connor et al, 2021; Liu et al, 2021). The current study demonstrates increased iNOS staining in the corpus callosum in each of these exposure groups (nPM, BCAS, and joint nPM + BCAS).…”
Section: Discussionmentioning
confidence: 93%
“…Here, the exposure to QDs is linked with an inflammatory response, as occurs following exposure to UFP. 49 For major details see S1.3 †…”
Section: Resultsmentioning
confidence: 99%
“…Looking at the analysis on mRNA and miRNA interactions, it could be hypothesized that the QDs, once inside THP-1 cells, determine the activation of the JAK/STAT and AKT signal cascades, resulting in the release of cytokines, including tumor necrosis factor α (TNFα), which is common to several inflammatory processes such as those consequent to exposure to environmental contaminants, 48 including nanoparticulates. 49 Indeed, since some of the physicochemical characteristics of nanomaterials and ultrafine particles (UFPs) can overlap, 50,51 such as size, exposure routes, and metal content, their toxicity mechanisms might also share common pathways and mechanisms. Here, the exposure to QDs is linked with an inflammatory response, as occurs following exposure to UFP.…”
Section: And Table S2 †)mentioning
confidence: 99%
See 1 more Smart Citation